Emergency Mosquito Control on a Selected Area in Eastern North Carolina after Hurricane Irene - Jonathan W. Harris; Stephanie L. Richards; Alice Anderson (SAGE Publishing, 2014)
Natural disasters such as hurricanes may contribute to mosquito abundance and, consequently, arbovirus transmission risk. In 2011, flooding from Hurricane Irene in eastern North Carolina (NC) resulted in increased mosquito populations that hindered recovery efforts. Budget shortfalls in NC have reduced the functionality of long-term mosquito surveillance and control programs; hence, many counties rely on the Federal Emergency Management Agency for post-disaster mosquito control. This pilot study examines mosquito abundance pre- and post-aerial insecticide spraying at eight study sites in Washington and Tyrrell Counties in rural eastern NC after Hurricane Irene. Percent change was calculated and compared for traps in areas that received aerial pesticide application and those that did not. Traps in spray zones show decreases in mosquito abundance when compared to control traps (treatment: -52.93%; control: 3.55%), although no significant differences (P = 0.286) were found in mosquito abundance between groups. Implications of reactive rather than proactive mosquito control responses are discussed.